2008
DOI: 10.4319/lo.2008.53.4.1479
|View full text |Cite
|
Sign up to set email alerts
|

The source and fate of organic matter and the significance of detrital pathways in a tropical coastal ecosystem

Abstract: Stable isotope analysis (SIA) and fatty acid profiling were used to elucidate the supply and fate of energy in a tropical coastal ecosystem in Hong Kong, southern China. To investigate seasonal changes in source supply on the diets of different trophic guilds, measurements were taken in three rocky bays before and after the onset of the summer monsoon, when supply of both marine macroalgal and streamborne terrestrial detritus increases. Particulate organic matter, comprising a mixture of marine and terrestrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
(55 reference statements)
2
19
0
Order By: Relevance
“…This suggests that queen conches can deplete much of their food resources even at low densities. While food sources were not quantified in the Xel-H谩 inlet, seasonal cycles may impact their quality/ availability (Medina-G贸mez & Herrera-Silveira 2006, Wai et al 2008). Further investigations would be required to determine in detail how variations in the food quality/availability may impact the movement of queen conches.…”
Section: Ontogenetic Variations Of Home Rangementioning
confidence: 99%
“…This suggests that queen conches can deplete much of their food resources even at low densities. While food sources were not quantified in the Xel-H谩 inlet, seasonal cycles may impact their quality/ availability (Medina-G贸mez & Herrera-Silveira 2006, Wai et al 2008). Further investigations would be required to determine in detail how variations in the food quality/availability may impact the movement of queen conches.…”
Section: Ontogenetic Variations Of Home Rangementioning
confidence: 99%
“…MDS then uses the ranks of similarities in an iterative process to find the spatial arrangement of samples that best represents the relationships among them (Clarke & Green 1988, Hair et al 2006. MDS is an exploratory analysis that does not take into account any a priori groups and so can be used to classify consumers with unknown diets (Howell et al 2003, Guest et al 2008 as well as to look for spatial (Hughes et al 2005, Fernandez-Jover et al 2007) and temporal (Wai et al 2008) differences in overall consumer FA composition. It has also been used to analyze the results of controlled feeding studies, both for comparing overall FA composition of animals on different diets (Kelly et al 2008(Kelly et al , 2009) and for tracking changes to FA composition over time (Hall et al 2006).…”
Section: Multivariate Statisticsmentioning
confidence: 99%
“…However, FAP and FA-specific d 13 C revealed that spatial, seasonal, and ontogenetic variations in shark diets were mainly attributable to changes in sources of detrital carbon, especially allochthonous sources. These detrital pathways could not be detected by SIA alone because its resolution is limited by the variety of detrital sources with similar stable-isotope sigantures in this complex environment (Kharlamenko et al 2001;Darnaude 2005;Wai et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Subsets of sharks (n 5 10) and prey samples (n 5 10) were lipid-extracted and the relationship between changes in d 13 C, % lipid (see below) and C : N ratio established, and used to correct the lipid effect on d 13 C using modeling methods (Post et al 2007). Stable isotope values for detritus from terrestrial, macroalgal (Sargassum hemiphyllum), and phytoplankton (i.e., particulate organic matter , 125 mm) sources were obtained from parallel studies (Wai et al 2008;T. C. Wai unpubl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation